2015
DOI: 10.1111/jbi.12468
|View full text |Cite
|
Sign up to set email alerts
|

Origin of the forest steppe and exceptional grassland diversity in Transylvania (central‐eastern Europe)

Abstract: Aim The forest steppe of the Transylvanian Plain is a landscape of exceptionally diverse steppe-like and semi-natural grasslands. Is this vegetation a remnant of a once continuous temperate forest extensively cleared by humans, or has the area, since the last glacial, always been a forest steppe? Understanding the processes that drive temperate grassland formation is important because effective management of this biome is critical to the conservation of the European cultural landscape.Location Lake Stiucii, no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
77
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 96 publications
(87 citation statements)
references
References 39 publications
10
77
0
Order By: Relevance
“…between 2200 and 1300 cal yr BP (Tóth et al, 2015). Our hydroclimate inference is supported by the reconstructions of low lake water level at Lake Ştiucii (Feurdean et al, 2013), and generally low lake levels recorded in central Europe (Magny, 2004), but contrasts with higher water levels at Lake Sfânta Ana (Magyari et al, 2009) and simulated slightly increase in growing season precipitation (Feurdean et al, 2015b). The DWT partly correlates with reconstructions from northern Poland that inferred a dry phase between 2250-25 2100 cal yr BP and wet shifts around 2750-2400 and 2000 cal yr BP (Lamentowicz et al, 2008).…”
supporting
confidence: 77%
See 1 more Smart Citation
“…between 2200 and 1300 cal yr BP (Tóth et al, 2015). Our hydroclimate inference is supported by the reconstructions of low lake water level at Lake Ştiucii (Feurdean et al, 2013), and generally low lake levels recorded in central Europe (Magny, 2004), but contrasts with higher water levels at Lake Sfânta Ana (Magyari et al, 2009) and simulated slightly increase in growing season precipitation (Feurdean et al, 2015b). The DWT partly correlates with reconstructions from northern Poland that inferred a dry phase between 2250-25 2100 cal yr BP and wet shifts around 2750-2400 and 2000 cal yr BP (Lamentowicz et al, 2008).…”
supporting
confidence: 77%
“…Our hydroclimate reconstruction agree with the low lake level and simulated high growing 23 season temperature and evapotranspiration for Transylvania before 6500 cal yr BP, but contrasts with the simulated increase in soil moisture conditions, and a decline in growing season temperature and evapotranspiration thereafter (Feurdean et al, 2015b).…”
supporting
confidence: 64%
“…In this way, canopy arthropods could be useful to predict the consequences of climate change, disturbances, or the loss of genetic diversity in oak forests. The use of canopy arthropods to examine the dynamics of the forest as well as alterations in vegetation cover by humans can be an efficient tool in time and cost compared to a longerterm perspective that implies information about palaeoecological record, pollen-based vegetation modeling, and biome reconstruction and global climate simulations (i.e., Feurdean et al 2015).…”
Section: Implications For Conservationmentioning
confidence: 99%
“…Fire, livestock grazing and agriculture have been detected during the late Holocene in a number of studies (Behre 1981;Kalis et al, 2003;Bradley et al, 2013;Kunes et al, 2015) and are suggested to have had a substantial impact on vegetation (Feurdean et al, 2015). These direct human impacts can potentially both demonstrate the human consequences of climate change and complicate interpretation of vegetation change in strictly climatic terms.…”
Section: Introductionmentioning
confidence: 99%